2019
DOI: 10.1101/682617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The common neoantigens in colorectal cancer are predicted and validated to be presented or immunogenic

Abstract: 23Colorectal cancer (CRC) is a malignant cancer with high incidence and mortality in the 24 world, as the result of the traditional treatments. Immunotherapy targeting neoantigens 25 can induce durable tumor regression in cancer patients, but is almost limited to 26 individual treatment, resulting from the unique neoantigens. Many shared oncogenic 27 mutations are detected, but whether the common neoantigens can be identified in CRC 28 is unknown. Using the somatic mutations data from 321 CRC patients combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Mayakonda et al have reported the high frequency of KRAS G12D mutations in pancreatic cancer [23,25]. Liang et al also demonstrated by mass spectrometry in 2019 that KRAS G12V-mutated neoantigen can be presented by HLA-A11:01 cell lines [28]. And as far as we know, clinical trials for KRAS G12V mutations in patients with HLA-A11:01 are already under way (NCT03190941).…”
Section: Comparison Of Neoantigens In Different Subtypes Of Crcmentioning
confidence: 99%
“…Mayakonda et al have reported the high frequency of KRAS G12D mutations in pancreatic cancer [23,25]. Liang et al also demonstrated by mass spectrometry in 2019 that KRAS G12V-mutated neoantigen can be presented by HLA-A11:01 cell lines [28]. And as far as we know, clinical trials for KRAS G12V mutations in patients with HLA-A11:01 are already under way (NCT03190941).…”
Section: Comparison Of Neoantigens In Different Subtypes Of Crcmentioning
confidence: 99%
“…Both G12D and G12V are highly mutated in multiple metastatic cancers, including Endometrial, CRC, and non-small cell lung cancer (Figure 4a-b). Witkiewicz et al have reported the high frequency of KRAS G12D mutations in pancreatic cancer [23,25]. Liang et al also demonstrated by mass spectrometry in 2019 that KRAS G12V mutated neoantigen can be presented by HLA-A11:01 cell lines [25].…”
Section: Hotspot Mutation-related Neoantigens That May Be a Potentialmentioning
confidence: 99%
“…Witkiewicz et al have reported the high frequency of KRAS G12D mutations in pancreatic cancer [23,25]. Liang et al also demonstrated by mass spectrometry in 2019 that KRAS G12V mutated neoantigen can be presented by HLA-A11:01 cell lines [25]. And as far as we know, clinical trials for KRAS G12V mutations in patients with HLA-A11:01 cancer are already under way (NCT03190941).…”
Section: Hotspot Mutation-related Neoantigens That May Be a Potentialmentioning
confidence: 99%
“…KRAS Gly12 (including G12V, G12C, and G12D) is a classic cancer mutation in multiple cancers including endometrial, colorectal cancer, and non-small cell lung cancer [30]. We previously reported high frequency mutations and high frequency neoantigens of G12D/V in gastric and colorectal cancer [14,31], our research group also demonstrated by mass spectrometry recently that KRAS G12V mutated neoantigen can be presented by HLA-A11:01 cell lines [32]. Previous studies have shown that gastrointestinal tumors, including esophageal cancer, gastric cancer, colon cancer and rectal cancer, have some similarities in tumor tissue origin and molecular characteristics [33], which are also reflected in this study, and high-frequency neoantigens in esophageal cancer are also similar to gastric cancer and colorectal cancer, suggesting the universality of neoantigen-based immunotherapy in gastrointestinal tumors.…”
Section: Neoantigens Shared Among Ec Patientsmentioning
confidence: 87%